Considerations on the Design of Space Structures - Active Design and Inclusion of Nonlinear Effects - Toklu, Yusuf Cengiz (ASCE - American Society of Civil Engineers, 2004)
Two approaches that should be important in designing space structures are discussed active design in contrast to passive design, and consideration of nonlinear effects in contrast to being limited by linearity It is stressed that use of these approaches will result in safer and lighter structures.
Engineering, Construction and Operations in Challenging Environments - Earth and Space 2004: Proceedings of the Ninth Biennial ASCE Aerospace Division International Conference --
Keywords: Deformation; Inclusions; Intelligent structures; Optimization; Space applications; Stress analysis; Lighter structures; Nonlinear effects; Passive design; Space structures; Structural design